A Binuclear Cobalt Complex in the Electrochemical Water Oxidation Reaction. Issue 13 (17th June 2022) - Nestke, Sebastian; Stubbe, Jessica; Koehler, Robert; Ronge, Emanuel; Albold, Uta; Vioel, Wolfgang; Jooss, Christian; Sarkar, Biprajit; Siewert, Inke
Abstract: The water splitting reaction represents an appealing approach to store solar energy. The 4e − /4H + oxidation of water generating O2 is considered as the bottleneck in this reaction and usually requires a rather large over potential. We report on the synthesis and application of a binuclear cobalt(III) complex, 1, with two μ‐OH ligands and tripodal triazole ligands, L, in the electrochemical water oxidation reaction (WOR; L=tris((1‐phenyl‐1H‐1, 2, 3‐triazol‐4‐yl)methyl)amine). The cobalt(III) centres in the complex exhibit an octahedral coordination geometry and the complex is stable in water. Electrochemical studies revealed that solutions of 1 NO3 catalyse the WOR in phosphate or borate buffer. However, further analysis showed, that 1 NO3 is a precursor and decomposes under the applied potential. A smooth deposit is formed on the electrode surface, which is a highly active water oxidation catalysis. The deposit consists of mainly cobalt oxide/hydroxide, which accounts for the catalytic activity, and small amounts of 1 NO3 . Abstract :